EXPERIMENTAL STUDIES ON FUEL PROPERTIES OF DIFFERENT BIODIESELS AND THEIR BLENDS WITH 2-PROPANONE - KAILAS M. TALKIT; D.T. MAHAJAN (International Journal of Pharma and Bio Sciences, 2016)
Biodiesels of different oils including mustard oil, sesame oil and cottonseed oil has been prepared. The fuel properties like acid value, density of diesel, different biodiesels and their blends with 2-Propanone were determined. From the present research work it’s found that acid value and density of biodiesels blends with acetone decreases linearly with increasing proportion of acetone while acid value and density of some pure biodiesel and their blends with acetone are found very close to diesel fuel value. Hence from above results it has been conclude that, fuel properties like acid value, density of biodiesels minimized by blending with renewable fuel such as 2-Propanone.